Assessing the Relations Between the South Sámi and Norwegian State in the Aftermath of the Fosen Case - Standal, Hedda Mortensen (2023)
This master's thesis explores and utilises the existing information regarding the preservation of Sámi reindeer herding culture in Norway and the demand for renewable wind energy, which emerged during and after the 2021 Fosen Supreme Court case. To widen my investigation, I have conducted a set of interviews with three strategically recruited informants who posed themselves as critical to the wind plants at Fosen and the court ruling. This was done to garner a deeper understanding of what ideas and perceptions they may have of the Fosen case, utilising these perspectives to inform my criminological approach to the case and its repercussions. I have found these insights, combined with a historical context and theoretical frameworks, to shed light on the strained relationship between the Norwegian state and the Indigenous South Sámi population residing in Norway. Additional points of interest raised in the aftermath of the Fosen case investigate the struggle of opposing interests of the Norwegian government; a state whose obligations to ensure Sámi protection and obtain climate neutrality through renewable energy projects struggle to co-exist, especially when one interest appears to triumph over the other. Ultimately, my thesis contributes to a growing literature on current Sámi-Norwegian relations, as well as controversies relating to the expansion of renewable energy plants in the criminological library. To contextualise and legitimise my research, I employ perspectives including critical-, green-, Southern- and postcolonial criminology, as well as perspectives to encapsulate the need for production and economic development through Treadmill of Production (ToP) theory.